2007
DOI: 10.1212/01.wnl.0000277487.04281.db
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline treatment in acute stroke

Abstract: Patients with acute stroke had significantly better outcome with minocycline treatment compared with placebo. The findings suggest a potential benefit of minocycline in acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
321
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 401 publications
(332 citation statements)
references
References 29 publications
6
321
1
4
Order By: Relevance
“…This pattern was apparent on day 7 of follow-up, and continued to day 30 [36]. Furthermore, there was no difference in the incidence of observed complications [36]. These findings prompted further study into the safety and dose range of minocycline [37].…”
Section: Stroke Trials Addressing Innate Immune Mechanisms Microglia mentioning
confidence: 90%
See 2 more Smart Citations
“…This pattern was apparent on day 7 of follow-up, and continued to day 30 [36]. Furthermore, there was no difference in the incidence of observed complications [36]. These findings prompted further study into the safety and dose range of minocycline [37].…”
Section: Stroke Trials Addressing Innate Immune Mechanisms Microglia mentioning
confidence: 90%
“…Minocycline is a second-generation derivative of tetracycline that has a protective effect in animal models of stroke through a variety of mechanisms, including anti-inflammatory effects, reduction of microglial activation, matrix metalloproteinase reduction, nitric oxide production, and inhibition of apoptotic cell death [36]. An open-label, evaluator-blinded study of 152 patients showed minocycline, when administered orally for 5 days at a dosage of 200 mg within 6 to 24 h of onset of stroke, to be associated with significantly lower National Institutes of Health Stroke Scale (NIHSS) score and modified Rankin Score (mRS) compared with placebo [36].…”
Section: Stroke Trials Addressing Innate Immune Mechanisms Microglia mentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, one of the authors' main conclusions was that the studies were heterogeneous [54]. To add to the confusion, a small number of controlled studies using Minocycline after acute stroke have to be considered [46,[49][50][51]. In these studies, minocycline, a second-generation tetracycline derivative that is not a first-or second-line antibiotic for most infections commonly present after stroke, was used not to prevent infections but to analyze its potential neuroprotective properties.…”
Section: Clinical Studies On Preventive Antibiotic Therapy After Strokementioning
confidence: 99%
“…The 4 studies on minocycline after acute stroke are not discussed in detail here [46,[49][50][51] (see Table 1). Remarkably, these studies, aimed at neuroprotection after stroke, used a narrower time window than the other studies No difference in pneumonia, and functional outcome/mortality after 90 days RCT = randomized controlled trial; i.m.…”
Section: Clinical Studies On Preventive Antibiotic Therapy After Strokementioning
confidence: 99%